High Prevalence of Adrenal Remnant Tissue in Patients Undergoing Bilateral Adrenalectomy for Cushing’s Disease - Wilson, Julian B.; Zopey, Mohan; Augustine, Jaimie; Schaffer, Randolph; Chiang, Manfred; Friedman, Theodore C. (Hormone and Metabolic Research, 2020)
Bilateral adrenalectomy (BLA) is a treatment option for patients with Cushing’s Disease (CD) if transsphenoidal pituitary surgery fails or is not a therapeutic option. For most patients, BLA eliminates endogenous glucocorticoid and mineralocorticoid production, but for a small number of patients, endogenous secretion of adrenal hormones from adrenal tissue continues or recurs, leading to signs and symptoms of hypercortisolism. If adrenal tissue is confined to the adrenal bed, it is considered adrenal remnant tissue, while if it is outside the adrenal bed, it is considered adrenal rest tissue. We retrospectively evaluated morning serum cortisol, nighttime serum cortisol, nighttime salivary cortisol, and 24-h urine free cortisol on at least three occasions in 10 patients suspected of having endogenous cortisol production. Imaging of adrenal remnant tissue was also reviewed. Ten of 51 patients who underwent BLA during this time period had adrenal remnant/rest tissue marked by detectable endogenous glucocorticoid production; 9 of the 10 patients had signs and symptoms of hypercortisolism. Localization and treatment proved difficult. We conclude that the incidence of adrenal remnant/rest tissue in those undergoing BLA following unsuccessful pituitary surgery was 12% although there may have been a selection bias affecting this prevalence. The first indication of remnant tissue occurrence is a reduction in glucocorticoid replacement with symptoms of hypercortisolism. If this occurs, endogenous cortisol production should be tested for by cortisol measurements using a highly specific cortisol assay while the patient is taking dexamethasone or no glucocorticoid replacement. Endocrinologists need to monitor the development of both adrenal remnant tissue and Nelson’s syndrome following BLA.
Keywords: Cushing's syndrome; remnant tissue; rest tissue; hypercortisolism; episodic; adrenalectomy